PENGARUH PEMBERIAN KOMPOS JERAMI DAN PUPUK SP-36 PADA TANAH SULFAT MASAM POTENSIAL TERHADAP PERUBAHAN SIFAT KIMIA SERTA PERTUMBUHAN DAN PRODUKSI PADI (Oriza sativa L.) - Herlina Eka Bhakari; Fauzi Fauzi; Hamidah Hanum (Jurnal Agroekoteknologi, 2013)
ABSTRACTThe objective of this research was to study the effect of rice straw compost and the application ofphosphorus fertilizer of SP-36 on chemical characteristic of acid sulphate soils, rice growth andproduction (Oryza sativa L). This research was conducted in greenhouse agricultural departments,Universities Northen Sumatera, Medan. This study used a randomized block design factorial, with2 factors : factor 1 : rice straw compost treatment (J) wich consist of : J0 = 0 ton ha-1(0 g straw/pot); J1 = 10 ton ha-1 (40 g straw/pot); J2 = 20 ton ha-1 (80 g straw /pot); J3 = 30 ton ha-1(120 g straw/pot). Faktor 2 : fertilizer phosphorus (P) which consist of : P0 = 0 kg SP-36 ha-1(0 g SP-36/pot); P1 = 0.5 dose (0.5 x 135 kg/ha), advice equal with 0,27 g SP-36/pot;P2 = 1,0 dose (1 x 135 kg/ha), advice equal with 0,54 g SP-36/pot; P3 = 1.5 dose (1.5 x 135 kg/ha),advice equal with 0,81 g SP-36/pot. This results of the research showed that rice straw composttreatment significantly affected C-organic, Fe2+ reduction, the maximum seedlings, dry weight ofroot. While the application of SP-36 fertilizer significantly affected the maximum seedlings.Combination of rice straw compost and fertilizer SP-36 significantly increased the maximumseedlings.Key words: acidic sulphate soil, straw compost, SP-36, rice